Analisis Kejadian Diare Pada Balita di Puskesmas II Kecamatan Tungkal Ilir - Suparmi, Suparmi; Fauziah, Rina; Siahaan, Sondang (NHM PRESS, 2024)
Diarrhea disease is a major problem as it can cause extraordinary events leading to death. The purpose of this study was to determine the factors associated with the incidence of diarrhea in children. This study used a descriptive analytic research method with a cross-sectional study approach conducted at Puskesmas II, Tungkal Ilir Subdistrict, Tanjung Jabung Barat District, involving 88 participants. The results of this study showed that 60 participants (68.2%) had primary education and 28 participants (31.8%) had education ≥ junior high school level. Among the mothers of children under five, 42 (47.7%) exhibited good behavior while 46 (52.3%) exhibited poor behavior. Regarding knowledge about diarrhea, 37 mothers (42%) had good knowledge and 51 (58%) had poor knowledge. Among mothers with primary education, 43 children suffered from diarrhea while 17 did not. The Chi-Square test results indicated that the incidence of diarrhea was not related to the level of education (p-value 0.740) and behavior (p-value 0.220), but it was related to knowledge (p-value 0.002). The incidence of diarrhea in children under five was not related to the level of education and behavior. There is a relationship between knowledge and the incidence of diarrhea in children under five in the Sriwijaya Subdistrict, Tungkal Ilir District, Puskesmas II Work Area.